Perceived Exertion in Small Sided-Games Internal Load Quantification in Wheelchair Basketball Players - Yanci J.; Calleja-González J.; Romaratezabala E.; Iturricastillo A. (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The present study seeks to analyse the physiological responses, differential perceived exertion and perceived load of wheelchair basketball (WB) players during a small sided games (SSG) and to analyse the existence or not of differences studied variables according to whether or not they have a spinal cord injury and the age of the players. This study makes a total of 128 observations of a single format SSG (4 vs. 4 players with a duration of 4 min). The players with a spinal cord injury obtain a lower mean heart rate (HR Mean) and a lower peak HR (HR Peak) in the SSG than players without a spinal cord injury (p < 0.001; ES = 0.9 to 1.1; large). However, players with a spinal cord injury show higher respiratory (RPE res) and muscular (RPE mus) perceived exertion than players without a spinal cord injury as well as record a higher respiratory (RPE res TL) and muscular (RPE mus TL) load (p < 0.001; ES = -0.7 to -0.8, moderate-large). Related to age groups, the results obtained demonstrate that players < 30 years old obtain higher HR Mean, HR Peak, tympanic temperature (p < 0.001; ES = -1.1; high), RPE res, RPE mus, RPE res TL and RPE mus TL (p < 0.001; ES = -0.7 to -0.9; moderate-large) than players > 30 years in the SSG. The impairment (whether they have a spinal cord injury or not) and the age of the players can affect the internal load in a SSG and the perceived exertion method can provide additional information about the load, especially among players with a spinal cord injury.